Austrian welfare economics: A reply to Wysocki and Megger - Wiśniewski, Jakub Bożydar (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In their article published in a recent issue of this journal, Wysocki and Megger (2019) attempt to undermine Rothbard’s welfare theory as articulated in his classic essay on the subject (2008). More specifically, they suggest that the theory in question generates some fatally counterintuitive conclusions and relies on viciously circular arguments. In this response, my aim is to demonstrate that while the article under consideration raises some interesting points, the rather monumental task that its authors set themselves — that is, the task of dismantling the whole of Austro-Rothbardian welfare economics — results in failure.
Keywords: welfare economics; Austrian economics; Rothbard, Murray Newton (1926-1995); property rights